FACTORS OF SUCCESS AND MOTIVATION OF RURAL ENTREPRENEURSHIP IN EASTERN SERBIA - Milovan Vuković; Igor Prvulović; Snežana Urošević (Ekonomika Poljoprivrede (1979), 2018)
This study examines success factors and motivation of entrepreneurs in the rural areas of the Eastern Serbia. The survey of the eighty entrepreneurs in the two municipalities has been conducted on the Zaječar district territory, and it included 14 villages. The weak economy, the depopulation process and the lack of financial sources are identified as problems, while the hard work and the quality of the products (services) are crucial success factors. On the other hand, political involvement had the lowest significance as the success factor. The results also indicate that the strongest motivators of the researched entrepreneurs were to be ones own boss and to increase ones own income.